Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Prove the following trigonometric identity

Asked by 16th April 2010, 7:08 PM
Answered by Expert
Answer:

cosecx - sinx = a3

1/sinx - sinx = a3

(1 - sin2x)/sinx = a3

cos2x/sinx = a3

(cos2x/sinx)2/3 = a2

Similarly,

(sin2x/cosx)2/3 = b2

Now, a2b2(a2+b2) =

[(cos2x/sinx)(sin2x/cosx)]2/3{(cos2x/sinx)2/3 + (sin2x/cosx)2/3} =

[cosx sinx]2/3{[(cos3x)2/3 + (sin3x)2/3 ]/(sinxcosx)2/3} =

[cosx sinx]2/3{[cos2x + sin2x ]/(sinxcosx)2/3} =

[cosx sinx]2/3{1/(sinxcosx)2/3} = 1.

Regards,

Team,

TopperLearning.

 

Answered by Expert 16th April 2010, 8:58 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp